EDUKASI DAN PELATIHAN PIJAT BAYI DENGAN BERAT LAHIR RENDAH - Rosmala Kurnia Dewi; Anggita Septyani Permatasari; Sehmawati; Pintam Ayu Yastirin (LPPM AN Nuur, 2023)
Background: Background: LBW cases are often associated with prematurity as the cause. There are many forms of intervention in handling LBW babies, one of which is providing intervention aimed at optimizing the growth and development of the baby, one of which is providing additional stimulation which includes touch and massage. Objective: The aim of providing health education and baby massage is to provide knowledge and skills to mothers to increase the weight of LBW babies. Method: The method used in this service is a descriptive survey with implementation techniques through history taking, documentation and observation of health education and massage for LBW babies. Results: After being given health education and baby massage, the average weight of LBW babies increased. Conclusion: The method of implementing health education and baby massage has been proven to help increase the weight of LBW babies at PMB Sri Lestari Ngembak.